2017
DOI: 10.3846/16111699.2017.1275283
|View full text |Cite
|
Sign up to set email alerts
|

Does a Connection Exist Among National Culture, Alliance Strategy, and Leading Ict Firms’ Performance

Abstract: "Corrigendum." Journal of Business Economics and Management, 18(1), p. 180

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…First, firms' performance prompts them to choose different cooperation strategies (Lant et al, 1992;Nohria and Gulati, 1996;Audia et al, 2000;Mezias et al, 2002;Fleming and Bromiley, 2003;Baum et al, 2005), such as a firm's propensity to engage in partnerships (Baum et al, 2005) and partner-selection strategies. Second, numerous characteristics of the context have been shown to play a role in shaping a firm's cooperation strategy; these characteristics include experienced uncertainty (Xie et al, 2012), national culture (Hofstede, 1984;Peng, 2005;Griffith et al, 2006;Siakas et al, 2010;Furres et al, 2012;Golonka and Rzadca, 2013) and generalized trust (Hofstede, 1984;Doney et al, 1998;Monczka et al, 1998;Young-Ybarra and Wiersema, 1999;Ibrahim and Ribbers, 2009). …”
Section: Formation Of Alliance Portfoliomentioning
confidence: 99%
See 4 more Smart Citations
“…First, firms' performance prompts them to choose different cooperation strategies (Lant et al, 1992;Nohria and Gulati, 1996;Audia et al, 2000;Mezias et al, 2002;Fleming and Bromiley, 2003;Baum et al, 2005), such as a firm's propensity to engage in partnerships (Baum et al, 2005) and partner-selection strategies. Second, numerous characteristics of the context have been shown to play a role in shaping a firm's cooperation strategy; these characteristics include experienced uncertainty (Xie et al, 2012), national culture (Hofstede, 1984;Peng, 2005;Griffith et al, 2006;Siakas et al, 2010;Furres et al, 2012;Golonka and Rzadca, 2013) and generalized trust (Hofstede, 1984;Doney et al, 1998;Monczka et al, 1998;Young-Ybarra and Wiersema, 1999;Ibrahim and Ribbers, 2009). …”
Section: Formation Of Alliance Portfoliomentioning
confidence: 99%
“…Studies have indicated that an extended, differentiated, complex, beneficial portfolio consisting of different alliances with various partners is a useful resource for carrying out a firm's strategy (Stuart, 2000;Lavie, 2007). A well-configured alliance portfolio has a positive impact on a firm's performance and innovativeness (Rothaermel, 2001;Rothaermel and Deeds, 2006;Shipilov, 2006;Lavie, 2007;Gulati, 2007;Duysters and Lokshin, 2011;Golonka, 2013;Golonka and Rzadca, 2013).…”
Section: Configuration Of Alliance Portfoliomentioning
confidence: 99%
See 3 more Smart Citations